The evolution of personal wealth in the Former Soviet Union and Central and Eastern Europe - Sergei Guriev; Andrei Rachinsky (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
This study discusses the evolution of personal wealth in transition economies. While data availability is still a problem, the available indirect evidence suggests privatization has resulted in an increase in personal wealth but also in personal wealth inequality, especially in the countries that lagged behind in building effective institutions. Another source of wealth inequality is the high income inequality due to wage decompression coupled with the low saving rates among the poor. We pay a special attention to one of the most noticeable implications of this rise in personal wealth and wealth inequality— the emergence of so called `oligarchs'. Using the comprehensive dataset of Muscovites' incomes we show that surveys that do not take into account the first- and second-tier rich (billionaires and millionaires) may drastically underestimate inequality. – inequality ; wealth distribution ; oligarchs ; privatization
Keywords: D31; O52; P36; 330; Einkommensverteilung; Vermögensverteilung; Oligarchie; Osteuropa; GUS-Staaten